2010
DOI: 10.4314/tjpr.v9i5.61050
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Perceptions of Healthcare Providers and Medical Students Towards Clinical Pharmacy Services in United Arab Emirates

Abstract: Purpose: To explore healthcare providers' (HCPs) and medical students' attitudes to, and perceptions of the pharmaceutical services that clinical pharmacists can provide in United Arab Emirates. Methods: A total of 535 participants (265 HCPs and 270 medical students) were asked to complete a questionnaire over a period of three months (January through March 2009). Results: Almost three quarters of the students perceived that the clinical pharmacist is an important part of the healthcare team while 82% believed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
46
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 17 publications
12
46
1
Order By: Relevance
“…The results of the current study resemble those of similar study done in this regard at united arab emirates UAE [12]. The results reinforced the fact that clinical pharmacist should communicate positively with physicians and show them their capabilities in direct patient care.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results of the current study resemble those of similar study done in this regard at united arab emirates UAE [12]. The results reinforced the fact that clinical pharmacist should communicate positively with physicians and show them their capabilities in direct patient care.…”
Section: Discussionsupporting
confidence: 86%
“…The questionnaire was written in English language and developed from review of the literature and previous studies relating to the clinical pharmacy services [12]. The survey questions were pre-tested by health care providers with extensive experience in clinical pharmacy services.…”
Section: Methodsmentioning
confidence: 99%
“…Clinical pharmacy is a recent area of practice in which pharmacist focus on patient oriented rather than drug oriented services. [1][2][3][4] Clinical pharmacy is the provision of proactive service where pharmacists directly interact in the patient care process through communicating with patients and other health care providers (HCPs). [3] Over the past two decades, a growing body of evidence has demonstrated that clinical pharmacy ensures better patient outcomes and improves patient quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Limited number of pharmacist employed as patient care provider as being clinical pharmacist (CP). [4,7,8] Unfortunately, clinical pharmacy services in UAE private and public health care settings are rare except Abu Dhabi and to certain extend in Dubai. [7,8] There is increasing evidence that the interaction between HCPs and CP ensure the goal of better patient outcomes, less therapeutic failure, more safe therapy and optimum cost effectiveness value.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning in this context that the first pharmacy college in the UAE was established only in 1992 and that only 2 postgraduate clinical pharmacy programmes are currently offered through colleges in UAE. A previous study done in the UAE had also reported a shortage of clinical pharmacists in UAE hospitals [12], with the very few available pharmacists deployed in hospitals managed by international institutions, such as Johns Hopkins Hospital and the Cleveland Clinic [13]. This lack of clinical pharmacists in UAE hospitals is similar to the situation in other countries, as reported by the Institute of Medicine in 2006, which demonstrated the need for clinical pharmacists as part of the ED team to improve safety but also recognized the lack of pharmacists as part of interdisciplinary emergency medicine teams at most institutions [14].…”
Section: Current Practicementioning
confidence: 99%